INHOMOGENEITIES OF CHEMICAL COMPOSITION AND COSMOCHRONOLOGY PROBLEMS - Klochkova, V. G.; Panchuk, V. E. (Одеські астрономічні публікації, 2017)
The problems of determination of chemical composition of stars and connection with theory of chemical evolution of Galaxy are discussed.